Film architecture and the transnational imagination set design in 1930s European cinema - Bergfelder, Tim (Amsterdam University Press, 2010)
Presents for the first time a comparative study of European film set design in the late 1920s and 1930
Keywords: Geschichte 1920-1940; Group work in art; Transnationalism; Motion pictures / Setting and scenery / Europe; Motion pictures / Europe / History / 20th century; Film, TV and radio; Society and social sciences; Society and culture: general; Motion pictures; Motion pictures; Setting and scenery; Filmarchitektur; ART; Film & Video; Europa; Europe; PERFORMING ARTS; Film & Video; Reference; History; The arts